The Influence of Brand Personality on Brand Trust: A Case Study of Hanasui Cosmetic Products - Irma Shantilawati; Ibnu Suryadi; Nurhadinah Nurhadinah (Oikonomia : Journal of Management Economics and Accounting, 2025)
This study aims to analyze the influence of brand personality on brand trust in the case of Hanasui cosmetic products. Brand personality refers to human-like characteristics associated with a brand, which can shape consumers' emotional perceptions and loyalty. Meanwhile, brand trust reflects the level of consumer confidence in the consistency, honesty, and benevolence of a brand. This research uses a quantitative descriptive approach with a survey method through questionnaires distributed to 120 respondents who are active users of Hanasui products. The sampling technique used is purposive sampling, and data analysis was conducted using simple linear regression with the help of SPSS software. The results show that brand personality has a positive and significant effect on brand trust. The most dominant dimensions of brand personality are sincerity and competence, while ruggedness was rated the lowest. The coefficient of determination (R²) was 0.513, indicating that 51.3% of the variation in brand trust can be explained by brand personality. These findings demonstrate that a strong and consistent brand personality can effectively build consumer trust, particularly for local cosmetic brands such as Hanasui.